Management reset : organizing for sustainable effectiveness - Lawler, Edward E., III (Jossey-Bass, 2011)
"Is not about convincing you that organizations need to be sustainably effective: it is a book about how organizations can be sustainably effective."--Excerpt from the Introduction.